2019
DOI: 10.1038/s41598-019-44990-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and mitochondrial responses to stress exposure suggest that king penguins are naturally equipped to resist stress

Abstract: Exposure to unpredictable environmental stressors could influence animal health and fitness by inducing oxidative stress, potentially through downstream effects of glucocorticoid stress hormones ( e.g . corticosterone) on mitochondrial function. Yet, it remains unclear whether species that have evolved in stochastic and challenging environments may present adaptations to alleviate the effects of stress exposure on oxidative stress. We tested this hypothesis in wild king penguins by inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 63 publications
3
37
0
Order By: Relevance
“…In this study, we have shown that an acute period of restraint‐induced stress resulted in a significant increase in DNA damage in house sparrows (Figures 2a and 3). This study extends previous findings that draw connections between acute stress and DNA damage in wild animals (Malandrakis et al, 2016; Stier et al, 2014, 2019). Although brief physiological doses of cortisol, epinephrine, and norepinephrine—which mimic aspects of the acute stress response—induce significant DNA damage within 10 min in vitro (Flaherty et al, 2017; Flint et al, 2007), cell culture and whole animal are very different experimental systems.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we have shown that an acute period of restraint‐induced stress resulted in a significant increase in DNA damage in house sparrows (Figures 2a and 3). This study extends previous findings that draw connections between acute stress and DNA damage in wild animals (Malandrakis et al, 2016; Stier et al, 2014, 2019). Although brief physiological doses of cortisol, epinephrine, and norepinephrine—which mimic aspects of the acute stress response—induce significant DNA damage within 10 min in vitro (Flaherty et al, 2017; Flint et al, 2007), cell culture and whole animal are very different experimental systems.…”
Section: Discussionsupporting
confidence: 92%
“…Malandrakis et al (2016) found that gilthead seabream ( Sparus aurata ) that were confined had elevated levels of DNA damage measured in liver cells within 1 min. In addition, acutely restrained king penguins ( Aptenodytes patagonicus ; 30 min) had increased levels of oxidative DNA damage markers in their plasma, but not their red blood cells (Stier et al, 2019). Finally, acute (24 hr) cold exposure in zebra finches ( Taeniopygia guttata ) increased oxidative DNA damage markers in plasma samples (Stier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would, therefore, like to emphasise that we only recorded data over a short time frame and encourage follow-up studies to measure the recovery from capture and handling induced stress over a more extended period. Moreover, additional measures for stress, representing different physiological aspects within the stress response such as oxidative stress, should be applied and tested in future studies (Costantini, 2008; Stier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While GiOS itself has not been studied in much detail, other studies in domestic chickens ( Gallus gallus ) and prairie voles ( Microtus ochrogaster ) have also demonstrated increased oxidative stress in response to an acute stressor in the form of increased levels of oxidative damage [7,20,28]. However, studies in wild king penguins ( Aptenodytes patagonicus [29]) and a captive population of house sparrows ( Passer domesticus [30]) saw either no significant change or even a decrease in oxidative damage levels in response to acute stress. We therefore need more research across diverse vertebrate taxa to determine the shared nature of the stress response and oxidative stress in order to better understand the extent to which GiOS is conserved.…”
Section: Discussionmentioning
confidence: 99%